Layanan Konsultasi Melalui Parental Mediation untuk Meningkatkan Literasi Digital Siswa - Yuyun Nuriyah Muslih (Institut Agama Islam Negeri Curup, 2022)
This study aims to describe consulting services through parental mediation strategies as an effort to improve students’ digital literacy. This is achieved through the library method by reading relevant data sources related to the themes of consulting services, parental mediation, and digital literacy. The information obtained is analyzed, recorded, and processed by in-depth content analysis and written in a narrative manner into the research results. The results of the study show that consulting services with parental mediation can be used to help improve students’ understanding of digital literacy. Service implementation is carried out through: (1) introduction stage; (2) situation description/ problem identification and analysis of problems; (3) the selection of solutions and how to use them; (4) demonstration of the selected solution; (5) conducting training and feedback; (6) giving homework; (7) evaluating the process and results and (8) terminating the consulting relationship. The implications of the study are to strengthen the role of school collaboration with parents in children's education and increase positive internet skills in students when learning at home.